2012
DOI: 10.1007/s00167-012-2161-9
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of patellofemoral osteoarthritis 12 years after anterior cruciate ligament reconstruction

Abstract: Risberg, M. A. (2013). The prevalence of patellofemoral osteoarthritis 12 years after anterior cruciate ligament reconstruction. Knee Surgery, Sports Traumatology, Arthroscopy, 21,[942][943][944][945][946][947][948][949] Dette er siste tekst-versjon av artikkelen, og den kan inneholde små forskjeller fra forlagets pdf-versjon. Forlagets pdf-versjon finner du på link.springer.com: http://dx.doi.org/10. 1007/s00167-012-2161-9 This is the final text version of the article, and it may contain minor differences… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
67
1
3

Year Published

2013
2013
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(75 citation statements)
references
References 49 publications
4
67
1
3
Order By: Relevance
“…More specifically, PF arthritis presents constantly with AKP, and other authors have documented that patients with established PF arthritis that required surgical treatment had a history of significantly higher AKP than controls (22 % vs 6 %, p<0.001) [48]. The risk of long-term arthritis after ACL reconstruction has been questioned in the literature, and the possibility of PF arthritis following ACL reconstruction has been recently re-emphasized [49][50][51]. Järvelä et al documented mild to severe PF osteoarthritis in 88.6 % of their patients seven years after ACL reconstruction [49] and also correlated the increased incidence of AKP in this group but, unfortunately, without evaluating for the presence of trochlear dysplasia in these patients [6].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…More specifically, PF arthritis presents constantly with AKP, and other authors have documented that patients with established PF arthritis that required surgical treatment had a history of significantly higher AKP than controls (22 % vs 6 %, p<0.001) [48]. The risk of long-term arthritis after ACL reconstruction has been questioned in the literature, and the possibility of PF arthritis following ACL reconstruction has been recently re-emphasized [49][50][51]. Järvelä et al documented mild to severe PF osteoarthritis in 88.6 % of their patients seven years after ACL reconstruction [49] and also correlated the increased incidence of AKP in this group but, unfortunately, without evaluating for the presence of trochlear dysplasia in these patients [6].…”
Section: Discussionmentioning
confidence: 99%
“…Järvelä et al documented mild to severe PF osteoarthritis in 88.6 % of their patients seven years after ACL reconstruction [49] and also correlated the increased incidence of AKP in this group but, unfortunately, without evaluating for the presence of trochlear dysplasia in these patients [6]. Oiestad et al documented 26 % of established PF arthritis 12 years after ACL reconstruction, again without checking for the pre-operative presence of similar radiological findings such as trochlear dysplasia [51]. Most recently, Culvenor et al reviewed the increased incidence of PF arthritis with ACL reconstruction and recommended prevention and treatment strategies with attention to rehabilitation protocols and quadriceps and hamstring muscles coordination in order to minimize this complication [50].…”
Section: Discussionmentioning
confidence: 99%
“…Several reports have revealed that PF-OA progresses after an ACL tear. The reported prevalence of PF-OA progression after ACL tear is 13-28 % [9][10][11][12]. Even after ACL reconstruction, PF-OA progression has been reported in short to mid-term follow-up periods [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…The reported prevalence of PF-OA progression after ACL tear is 13-28 % [9][10][11][12]. Even after ACL reconstruction, PF-OA progression has been reported in short to mid-term follow-up periods [10,11]. However, many reports of PF-OA after ACL tear or reconstruction include follow-up data of less than 20 years [10][11][12][13][14][15][16][17][18], and the evaluation of PF-OA in elderly subjects without ACL function has not been well investigated.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation